1994
DOI: 10.1111/j.1476-5381.1994.tb14803.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NK1 and NK2 tachykinin receptors in guinea‐pig and rat bronchopulmonary and vascular systems

Abstract: 1 NK1 and NK2 tachykinin receptors were characterized in guinea-pig and rat bronchopulmonary systems and in the vasculature of the rat by use of radioligand binding and/or functional studies.2 The radioligands for NKI and NK2 receptors ([3H]-SP and [3H]-pNKA, respectively) did not label tachykinin receptors in homogenates of rat lungs or bronchi. In contrast, in the guinea-pig, [3H]-SP bound with high affinity to these tissues (KD = 0.23 ± 0.08 nM and 0.34 ± 0.05 nM, for lungs and bronchi, respectively). The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Whether EDC and EDR are mediated by the same NK1 receptor remains to be clarified. NK1 receptors in the guinea-pig bronchopulmonary system and rat vascular system are different pharmacologically (Floch et al, 1994). We have found that unlike EDC, naturally occurring tachykinins all cause EDR according to the rank order of potency SP > NKA > NKB (unpublished data).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Whether EDC and EDR are mediated by the same NK1 receptor remains to be clarified. NK1 receptors in the guinea-pig bronchopulmonary system and rat vascular system are different pharmacologically (Floch et al, 1994). We have found that unlike EDC, naturally occurring tachykinins all cause EDR according to the rank order of potency SP > NKA > NKB (unpublished data).…”
Section: Discussionmentioning
confidence: 82%
“…The presence offunctional NK1 receptors on the endothelium has been demonstrated in human umbilical arteries (Greeno et al, 1993). The tachykinin receptor mediating EDR is also the NK1 subtype in guinea-pig and rabbit pulmonary arteries (Emonds-Alt et al, 1993;Floch et al, 1994). Whether EDC and EDR are mediated by the same NK1 receptor remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dose of SP needed to produce a marked increase in P pa was much larger than that required in the isolated guinea pig lung (20) or the isolated rabbit pulmonary arterial strip (23). This difference might be due mainly to fewer NK 1 receptors in the rat lung than in the guinea pig lung (8). In addition, there might be a difference in NK 1 receptors between the rat and the guinea pig lungs (8).…”
Section: Discussionmentioning
confidence: 96%
“…This difference might be due mainly to fewer NK 1 receptors in the rat lung than in the guinea pig lung (8). In addition, there might be a difference in NK 1 receptors between the rat and the guinea pig lungs (8).…”
Section: Discussionmentioning
confidence: 99%
“…SP causes endothelium-dependent relaxation (EDR) through the production of nitric oxide (NO) via NK 1 receptors in pre-contracted guinea-pig and rabbit pulmonary arteries (D'Orleans-Juste et al, 1986;Emonds-Alt et al, 1993;Floch et al, 1994) and endothelium-independent contraction (EIC) via NK 2 receptors in non-contracted rabbit pulmonary arteries (D'Orleans-Juste et al, 1986). We have reported that SP causes endothelium-dependent contraction (EDC) via NK 1 receptors and the production of TXA 2 at low concentrations and EIC via NK 2 receptors at higher concentrations in the distal portion of rabbit intrapulmonary arteries (Shirahase et al, 1995).…”
Section: Introductionmentioning
confidence: 99%